(untitled) (Nordic Journal of African Studies, 2003)
This article is a response to Gromov’s article entitled Nagona and Mzingile: Novel, Tale or Parable? Contrary to Gromov’s thesis on the structural ambiguity of the novel, we posit that the structure of this novel is discernible if we consider the fluidity of the genre ’novel’ and if we bring in elements of socio-cultural patchwork and chaos characterising contemporary African societies. This article argues that the idea of fragmentation which is revealed at the level of an individual and society in the novel, goes very well with its fictional devices. In fact the fictional devices render the discourse of the novel disruption. It is a double-edged design pregnant on the one hand, with religious, philosophical, political and social rhetoric for its literary substance and on the other, ’orality’ and ’magic realism’ for its fictional strategies which seem to cause ’fragmentariness’ that challenge the traditional method of narration with simple temporal linearity.